2018
DOI: 10.1002/jssc.201800545
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of savaside A, acteoside, and isoacteoside in rat plasma by UHPLC–MS/MS: Comparative pharmacokinetic and bioavailability characteristics of Monochasma savatieri via different routes of administration

Abstract: Phenylethanoid glycosides are the bioactive components in Monochasma savatieri that primarily contains savaside A, acteoside, and isoacteoside. Pharmacological research has been comprehensive, but there have been few studies on pharmacokinetics, especially about savaside A. An ultra high performance liquid chromatography with tandem mass spectrometry with multiple reaction monitoring mode was developed and validated for the simultaneous determination of the three compounds from M. savatieri. Meanwhile, this me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Therefore, verbascoside may be used as a potential candidate against infections of bacteria that produce CDCs. However, after 50 mg/mL verbascoside was intramuscularly injected into rats, the C max in mice was approximately 20,000 ng/mL (Feng et al, 2018), which indicated that the bioavailability of this compound was relatively low. Thus, further studies should be performed to improve the bioavailability of verbascoside.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, verbascoside may be used as a potential candidate against infections of bacteria that produce CDCs. However, after 50 mg/mL verbascoside was intramuscularly injected into rats, the C max in mice was approximately 20,000 ng/mL (Feng et al, 2018), which indicated that the bioavailability of this compound was relatively low. Thus, further studies should be performed to improve the bioavailability of verbascoside.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that verbascoside has many biological and pharmacological effects, such as anti-inflammatory, antioxidant, antibacterial, antitumor, antifungal, and chelation properties, and can be used in skin cosmetics and topical preparations ( Mazzon et al, 2009 ; Kostyuk et al, 2011 ; Vertuani et al, 2011 ; Etemad et al, 2016 ). Other reports have shown that verbascoside can be fully absorbed within 1 h and reach a high blood concentration and that its bioavailability on delivery via various injection methods does not exceed 25% ( Dai et al, 2017 ; Feng et al, 2018 ). Based on the aforementioned pharmacological activities, this study found and studied the inhibitory effects of verbascoside on gas gangrene through a series of in vitro and in vivo experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The bioavailability order of the three PhGs appears to be verbascoside > isoverbascoside > savaside A. 76 Zhang et al investigated the pharmacokinetic of four PhGs (verbascoside, isoverbascoside, martynoside, and crenatoside) after orally administrated 10.0 g crude Acanthus ilicifolius herb per kg to rats. Although the four PhGs share similar molecular structures, they displayed different elimination half-lives (T 1/2 ), and different areas under the curves (AUC 0-t ), ranging from 3.4 to 9.0 h, and 1826.3 to 23.6 μg/L•h, respectively.…”
Section: F I G U R Ementioning
confidence: 99%
“…The main pharmacokinetic parameters of several PhGs in plasma are summarized in Table 3. [70][71][72][73][74][75][76]78,[189][190][191][192][193][194]…”
Section: Pharmacokinetics Of Phgsmentioning
confidence: 99%
“…Most herbal medicines are administered orally, and the components are inevitably metabolized before absorption from the gastrointestinal tract; however, poor oral absorption of PhGs was observed in a Caco-2 cell monolayer model, suggesting poor intestinal permeability (Gao et al, 2015; Zhou et al, 2018). A low blood drug concentration and relatively rapid metabolism of PhGs were observed after dosing in previous pharmacokinetic studies (Qi et al, 2013; Deng et al, 2014; Li et al, 2015a; Cui et al, 2016a; Li et al, 2016a; Su et al, 2016; Cui et al, 2017; Feng et al, 2018; Qian et al, 2018); however, these existing results are inadequate to fully understand the metabolic process and the mechanism underlying the pharmacologic activities. An in vitro digestion model provides a useful platform for fast and reproducible assessment of herbal medicine metabolism (Payne et al, 2012; Kang et al, 2013; Xu et al, 2017; Cui et al, 2018; Zhang et al, 2018; Feng et al, 2019).…”
Section: Introductionmentioning
confidence: 97%